Contingency effects of firm structure and environmental uncertainty on strategic planning process and firm performance: Evidence from UAE enterprises. (4th March 2020) - Chaib Lababidi, Houyem; Lababidi, Reem; Colak, Mustafa; Dayan, Mumin
Abstract: Previous research has reported inconsistent findings concerning the relationship between strategic planning and organizational performance and pointed out that a reason for this ambiguity is the fact that most research has traditionally focused on the direct effects of strategic planning on performance, taking insufficient consideration of the influence of several contextual variables on this relationship. Following this observation, this study adopts the perspective of contingency theory and develops six hypotheses predicting that strategic planning is positively related to organizational performance only when the two contextual variables of organizational structure and environmental uncertainty are aligned individually and jointly with the strategic planning process. Data were collected on senior executives and managers involved in formulating strategies in the United Arab Emirates (UAE) enterprises and analyzed by using multiple regression analysis involving moderated moderation. Results supported all the six hypotheses, confirming the central assumption of the present study that, at least in the UAE setting, a holistic or multivariate fit approach to contingency theory can shed light on the planning–performance relationship. The theoretical and managerial implications of the study findings are finally discussed.